Costs of Maternal Health-related Complications in Bangladesh (Journal of Health, Population and Nutrition, 2012)
This paper assesses both out-of-pocket payments for healthcare and losses of productivity over six months    postpartum among women who gave birth in Matlab, Bangladesh. The hypothesis of the study objective    is that obstetric morbidity leads women to seek care at which time out-of-pocket expenditure is incurred.    Second, a woman may also take time out from employment or from doing her household chores. This loss    of resources places a financial burden on the household that may lead to reduced consumption of usual    but less important goods and use of other services depending on the extent to which a household copes    up by using savings, taking loans, and selling assets. Women were divided into three groups based on their    morbidity patterns: (a) women with a severe obstetric complication (n=92); (b) women with a less-severe    obstetric complication (n=127); and (c) women with a normal delivery (n=483). Data were collected from    households of these women at two time-pointsat six weeks and six months after delivery. The results    showed that maternal morbidity led to a considerable loss of resources up to six weeks postpartum, with    the greatest financial burden of cost of healthcare among the poorest households. However, families coped    up with loss of resources by taking loans and selling assets, and by the end of six months postpartum, the    households had paid back more than 40% of the loans.   DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11315   J HEALTH POPUL NUTR 2012 Jun;30(2):205-212